The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7326/m18-1670
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pulmonary Embolism During Pregnancy

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 39 publications
1
57
2
4
Order By: Relevance
“…Few patients in this study population, only 4%, received a diagnosis of pulmonary embolism, similar to the prevalence found in other studies including pregnant patients. 1,2 In this case, the negative predictive value was 99.5%. However, the prevalence in studies conducted in the United States appears lower, at 2.8%, compared with just over 5% in other countries.…”
Section: Discussion Pointsmentioning
confidence: 72%
“…Few patients in this study population, only 4%, received a diagnosis of pulmonary embolism, similar to the prevalence found in other studies including pregnant patients. 1,2 In this case, the negative predictive value was 99.5%. However, the prevalence in studies conducted in the United States appears lower, at 2.8%, compared with just over 5% in other countries.…”
Section: Discussion Pointsmentioning
confidence: 72%
“…27 Diagnostic criteria for the management of suspected pulmonary embolism in pregnant women have largely been gleaned from studies in nonpregnant populations and retrospective studies and, thus, remain inconsistent and under debate. 29 Most guidelines recommend the use of V/Q scan over chest CT, primarily to minimize maternal radiation exposure. 30 However, a recent study 29 in 2018 reported high performance of a CT-based diagnostic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and the postpartum period confer an increased risk of venous thromboembolism, but only 4-7% of women investigated are diagnosed as having pregnancy associated pulmonary embolism 5051. Diagnosing pulmonary embolism in pregnancy is challenging, as shortness of breath and lower extremity swelling are common complaints and D-dimer concentration is increased in normal pregnancies.…”
Section: Diagnosismentioning
confidence: 99%
“…Two large observational studies specific to pregnant women have recently been published. The first evaluated the use of the modified Geneva score and a high sensitivity D-dimer in 441 pregnant patients 51. Women with a low or intermediate clinical probability and negative D-dimer (<500 μg/L) had pulmonary embolism excluded; all others underwent bilateral lower limb compression ultrasonography and, if this was negative, CTPA.…”
Section: Diagnosismentioning
confidence: 99%